GREEN SYNTHESIS OF PYRAZOLO [3,4]-PYRIMIDINE-THIONES USING IONIC LIQUID 2-METHYL-IMIDAZOLIUM-OXALATE AS POTENT EHRLICH ASCITES CARCINOMA RECEPTOR ANTAGONISTS - GANESH N YALLAPPA; NAGARAJA D; CHANDRASHEKHAR U (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Pyrazolopyrimidines are heterocyclic molecules containing nitrogen as the main composition, and hence, they exhibit pharmacological efficacy. They are analogs of purines so that possessing wide applications in the field of medicinal chemistry. The main objective of this study is to synthesize different derivatives of pyrazole-pyrimidine classes by adopting simple methodology as well as by employing green chemistry. The purpose of the synthesis of these molecules is to study the antitumor activity against Ehrlich ascites carcinoma (EAC) cell lines. Methods: After literature studies, it makes us to involve in the research of synthetic organic chemistry, especially to synthesize new compounds of pyrazolopyrimidines. We are reported solvent-free synthesis of pyrazolo [3,4-d]-pyrimidine-thiones through ethyl acetoacetate, hydrazine hydrate, thiourea, and different benzaldehydes. An ionic liquid 2-methyl-imidazolium-oxalate catalyzed the reactions under ultrasonication bath. Both conventional and ultrasonic methods were employed and comparison studies have been made. It was found that ultrasonic method completed the reaction quicker than the conventional method. All the synthesized compounds were confirmed their structures by 1HNMR, Fourier transform infrared, 13C-NMR, and elemental analysis spectra. The compounds were tested for in vitro anticancer activity against EAC cell lines. Most compounds revealed significant anticancer activity relative to doxorubicin as a positive control with inhibitory concentration (IC50) values. Results: Ultrasonication method is a simple method under which all the reactions were completed at faster time (<7 min) compared to the convention method. Among eight molecules, 8a and 8d completed the reactions at a faster rate. We reported IC50 values of all the molecules, in which 8e and 8g were exhibited excellent potency against EAC cell lines at different concentrations . Conclusions: Ultrasonication method is an excellent method for the organic synthesis. We are herein reported that under this method, all the reactions are completed within 7 min. Hence, it is superior method than the conventional method. All synthesized molecules have shown good inhibitor potency against EAC cell lines. Among them, two molecules 8e and 8g have shown excellent inhibitor potency.